SIFAT FISIK DAN MORFOLOGI KOMPOSIT KARBON AKTIF TONGKOL JAGUNG - Maulana Sanwijaya; Afira Ainur Rosidah; Muhammad Yunus (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Corn cobs are included in agricultural waste that is not utilized optimally. This organic waste is one of the right candidates to be used as activated carbon with various promising uses. This is the background for this research to make activated carbon from corn cobs which is activated using ZnCl2 with activator variations of 0, 8, and 16%. FTIR testing was performed to confirm the functional groups that appeared on the carbon from corn cobs before and after activation. Additionally, the activated carbon that successfully made was mixed with sago starch in a ratio of 75:25 to become a composite and to make it easier to fabricate the sample. Then SEM-EDX characterization, water content and ash content were carried out. The results of the FTIR test showed that the addition of the ZnCl2 activator caused the appearance of hydroxyl groups. In the water content, the results showed that the higher the activator concentration, the higher the water content. Meanwhile, the higher the activator used in activated carbon, the lower the ash content. SEM testing showed an enlargement of pore size and uniformity with increasing ZnCl2 concentration and EDX results showed an increase in the percentage of O elements.